Innovative strategies in designing the micro-credentials module / Norbaiti Tukiman ... [et al.] - Tukiman, Norbaiti; Set, Foong Ng; Ab Jabal, Mohamad Faizal; Mohamad Yunos, Nurhazirah; Ahmad, Nur Intan Syafinaz; Khalid, Ahmad Khudzairi; Din, Rosseni; Samsudin, Surieyani (Universiti Teknologi MARA, Perlis, 2022)
The twenty-first century is marked by rapid and disruptive change. In such a fast-paced economy, individuals either workers or students must be able to reskill and upskill in order to stay on top of it. However, not everyone has the opportunity to enter a higher education institution to obtain the certificate for the required skills. Thus, Micro-Credential Courses are the solution to develop one's skills and they are eligible for everyone. Therefore, this research aims to present a unique and innovative strategy to develop and manage the process of designing Micro-Credentials module in Mathematics topic, specifically Functions. The observational study is applied to analyse the strategy in developing the modules developed by the educators in Universiti Teknologi MARA Campus Johor. The educators have proposed a series of strategies in developing the Micro-Credentials module based on the basic principles recommended by Malaysian Qualifications Agency, namely outcome-based, personalised, on-demand, transparent, secure and shareable. The findings revealed that the Micro-Credentials developed and designed based on these basic principles is suitable to be implemented in online distance learning. The designed module provides shorter duration course, flexible education model and enable workers or students to reskill and upskill on a particular mathematics topic.